2009
DOI: 10.3998/ark.5550190.0010.106
|View full text |Cite
|
Sign up to set email alerts
|

Hydrazinecarbothioamide group in the synthesis of heterocycles

Abstract: The review summarizes recent literatures dealing with hydrazinecarbothioamide group in thiocarbohydrazides and other derivatives including their physical and chemical properties along with their applications in the synthesis of heterocycles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 40 publications
(15 citation statements)
references
References 20 publications
0
15
0
Order By: Relevance
“…18,19 Previously, we utilized by N,N'-disubstituted-hydrazinecarbothioamides in heterocyclic synthesis, such as 1,3-thiazin-2-ylidene-substituted hydrazides and 1,2,4-triazolo [3,4-b]-1,3-thiazine-5-carboxylates 20 . Continuation of our research program included the synthesis of various thiazoles, [21][22][23][24][25][26] we herein report the results of our investigation on the reactions of symmetrical hydrazinecarbothioamides 1a-d with 2-bromoacetophenones 2a,b.…”
Section: Introductionmentioning
confidence: 99%
“…18,19 Previously, we utilized by N,N'-disubstituted-hydrazinecarbothioamides in heterocyclic synthesis, such as 1,3-thiazin-2-ylidene-substituted hydrazides and 1,2,4-triazolo [3,4-b]-1,3-thiazine-5-carboxylates 20 . Continuation of our research program included the synthesis of various thiazoles, [21][22][23][24][25][26] we herein report the results of our investigation on the reactions of symmetrical hydrazinecarbothioamides 1a-d with 2-bromoacetophenones 2a,b.…”
Section: Introductionmentioning
confidence: 99%
“…Melting points are uncorrected values. 1 H NMR and 13 C NMR spectra (Bruker AM 400, 1 H: 400.13 MHz, 13 C: 100.6 MHz) were obtained from CDCl 3 solutions; the chemical shifts (δ) are given relative to internal standard TMS, and coupling constants (J) are in Hz. For preparative thin layer chromatography (PLC), glass plates (20 × 48 cm) were covered with a slurry of silica gel Merck PF 254 and air dried using the solvents listed for development.…”
Section: Methodsmentioning
confidence: 99%
“…The 1 H NMR spectrum of 4a showed the fused phenyl protons at d H = 7.90 (t, 2 H, J = 7.0 Hz) and 7.85 (d, 2 H, J = 7.8 Hz), whilst two NH-protons were observed as broad singlets at d H = 6.5 and 8.0. The observed 13…”
mentioning
confidence: 94%
See 1 more Smart Citation
“…They are also ideal candidates and valuable building blocks for the synthesis of different families of heterocyclic compounds. [14][15][16][17] Many diseases such as cancer may be treated by using thiosemicarbazides and thus their development is still in progress. 18,19 It has been reported that 4-substituted thiosemicarbazides 1a-c (Scheme 1) reacted with tetracyanoethylene (TCNE, 2) in ethyl acetate with admission of air to give thiadiazepine and pyrazolothiadiazole derivatives as well as 3-amino-4,5-dicyanopyrazole.…”
Section: Introductionmentioning
confidence: 99%